Numerical Analysis of the Effect of Serrated Fin to the Heat Transfer in the Condenser - Lohdy Diana; Febrian Kusumawardani; Wahyu Nur Fadilah; Muhammad Nabiel Ariansyah; Muhammad Farid Irfianto (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2021)
Condenser is one of the most important components in the power generation industry, which serves to condense the output steam from low-pressure turbine for boiler feed water. Several ways can be used to improve the performance of the condenser, one way is to add a serrated fin on the outer tube to lower the temperature of the outlet. A serrated fin that is used has 0° and 30 segments per period, which is installed on the tube with the diameter of the outer of 0.03175 m. This research was carried out by using the numerical method of CFD 2D to compare the performance of the heat transfer on the tube without and with a serrated fin on the variation speed of 7 m/s and 9 m/s. By inputting the parameters of the inlet of 350.15 °K, the resulting value of the outlet serrated fin tube temperature which is lower than the annular tube (tube without the serrated fin). On the simulation of the serrated fin tube with an inlet velocity of 7 m/s resulting outlet temperature of 343.2 °K, lower than in the simulation on the annular tube which produces the outlet temperature of 344.53 °K.